Chemiluminescent 2-Coumaranones: Synthesis, Luminescence Mechanism, and Emerging Applications - Stefan Schramm; Tim Lippold; Isabelle Navizet (Molecules)
Recently, 2-Coumaranones have emerged as a highly promising class of chemiluminescent compounds, distinguished by their unique structural properties that facilitate efficient light emission. This review provides a comprehensive analysis of their synthesis, structural characteristics, and chemiluminescence mechanisms, integrating historical perspectives with the latest advancements in the field. Beyond their intrinsic photophysical and chemical properties, 2-coumaranones have demonstrated broad utility across bioanalytical and material sciences. Notable applications include enzyme-catalyzed chemiluminescence in aqueous systems, glucose and urease-triggered detection assays, and mechano-base-responsive luminescence for stress sensing. Additionally, recent developments in chemiluminescent protective groups and their incorporation into advanced functional materials underscore the versatility of these compounds. Despite significant progress, key challenges remain, particularly in optimizing quantum yield, emission properties, and solvent compatibility for practical applications. Future research should prioritize the development of highly tunable 2-coumaranone derivatives with enhanced spectral and kinetic properties, further expanding their potential in diagnostics, bioimaging, and mechanoluminescent sensing. By addressing these challenges, 2-coumaranones could pave the way for next-generation chemiluminescent technologies with unprecedented sensitivity and adaptability.